Pro Spring MVC with WebFlux web development in Spring framework 5 and Spring boot 2 - Deinum, Marten; Cosmina, Iuliana (Apress, 2020)
Explore the designs of the Spring MVC and WebFlux frameworks, and apply similar designs and techniques to your own code. Along with detailed analysis of the code and functionality, this book includes numerous tips and tricks to help you get the most out of Spring MVC, WebFlux, and Java-based web application development in general using Spring. You'll see how Spring MVC is a modern web application framework built upon the latest Spring Framework 5 and Spring Boot 2. Spring MVC is suitable for building reusable web controller modules that encapsulate rich page navigation rules. Pro Spring MVC with WebFlux takes great care in covering every inch of Spring MVC with WebFlux to give you the complete picture. Along with all the best-known features of these frameworks, you'll discover some new hidden treasures. You'll also learn how to correctly and safely extend the frameworks to create customized solutions. This book is for anyone who wishes to write robust, modern, and useful web applications with the Spring Framework. After reading and using this book, you'll become proficient with Spring MVC and be able to apply it to your own Java web applications and microservices. What You Will Learn Use Spring MVC with WebFlux to build Java-based web applications Employ the various Spring MVC architectures Work with controllers and routing functions Build microservices and web services using Spring MVC and REST Create reactive web applications using Spring WebFlux Secure Spring MVC and Spring WebFlux Deploy your Spring MVC application to the cloud Who This Book Is For Those with at least some prior experience with Java web application development. Some previous experience with Spring Boot or the Spring Framework is recommended.
Includes index. - Online resource; title from PDF title page (SpringerLink, viewed March 11, 2021)
Keywords: Application software -- Development; Web site development; Java (Computer program language); Logiciels d'application; Développement; Sites Web; Développement; Java (Langage de programmation); Application software; Development